Research on the influence of perceived quality on users’ continuance usage intention of online live streaming class platforms: the mediating role of flow experience and the moderating impact of perceived usefulness - Wu, Fan; Xie, Guangying (Frontiers in Psychology, 2024)
Background With the penetration of the “Internet+” into social life, the digitization of education has become a trend and national demand. Alongside the rise of the “Everyone Live Streaming” era, online live streaming class platforms have rapidly grown due to favorable user experiences. Methods Grounded in the Expectation Confirmation Theory, this study employed questionnaire surveys to investigate the influence mechanism of perceived quality, flow experience, and perceived usefulness on individuals’ continuance usage intention of online live streaming class platforms. Results Through the analysis of 773 survey responses, this study reveals several key findings. Firstly, perceived quality significantly and positively affects users’ intention to continue using the online live streaming class platforms. Secondly, flow experience partially mediates the relationship between perceived quality and continuance usage intention, underscoring its significance in user decision-making. Additionally, Perceived usefulness negatively moderates the relationship between perceived quality and flow experience, demonstrating varied effects. Conclusion On the one hand, online live streaming platforms should actively invest in improving the quality of user perception, as this can lead to a better user flow experience and continued willingness to use. On the other hand, they should also pay more attention to the user’s flow experience, which has a direct impact on the user’s propensity to continue to use. Besides, the perceived usefulness of the online live class by the user should also be taken seriously.